Comparison criteria between matching algorithms texts application on (horspool's and brute force algorithms) - Ibrahim, Amin Mubark Alamin; Mustafa, Mustafa Elgili (Journal of Advanced Computer Science & Technology, 2015)
The subject of matching text or search the texts is important topics in the field of computer science and is used in many programs such as Microsoft word program in correct spelling mistakes and search &replace, and other uses. The aim of this study was to learn how to trade-off texts matching algorithms, which are very much where we have the application on Horspool's and Brute Force algorithms. According to the standard number of comparisons and time of execution. The study pointed on preference Horspool's algorithm.